Assessment of energy losses in power distribution systems with individual prosumers and energy communities. Issue 3 (3rd March 2023) - Diahovchenko, Illia; Petrichenko, Lubov
Abstract: Achieving the energy transition target will require the extensive engagement of consumers and the private sector in investment and operation of renewable‐based power systems. Support of individual prosumers and proliferation of energy communities are efficient ways to implement this engagement. To facilitate smooth integration of prosumers with photovoltaic (PV) installations, while satisfying effective operation of the power distribution system (PDS), it is important to fundamentally assess energy losses for different grid development scenarios. In this paper, the energy losses are compared for two alternatives: (a) when prosumers with PV installations act as individual grid users, and (b) when prosumers become participants of a solar energy community. To achieve this goal, modeling of loads, prosumers' behavior and PV generation was performed. Furthermore, it has been analyzed how the physical topology of the distribution network can be harmonized with the underlying bidirectional power flows for each alternative, while complying with system constraints. The IEEE 123 Node Test Feeder was employed to capture the performance of the PDS and to estimate the energy loss with various penetration levels of prosumers. The results indicate that reduction of energy losses is only possible until a certain PV penetration level, after which additional PV capacities cause increase in energy losses and complicate the PDS's operation. Lower energy losses were supervised for the cases with dispersed PV generation, compared to the cases focused on energy communities. This means that the PDS demonstrates better tolerance to evenly distributed prosumers, rather than to single sources of a larger scale installed in one node. The outputs of this study will help the energy planners and utilities in improving performance of the PDS in terms of loss minimization and loadability maximization. Abstract : Achieving the energy transition target will require the extensive engagement of consumers and the private sector in investment and operation of renewable‐based power systems. Support of individual prosumers and proliferation of energy communities are efficient ways to implement this engagement. In this paper, the energy losses are compared for individual prosumers with photovoltaic installations and for solar energy community.